2020
DOI: 10.1007/s00592-020-01626-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical activity promotion on adiponectin, leptin and other inflammatory markers in prediabetes: a systematic review and meta-analysis of randomized controlled trials

Abstract: Aims Inflammatory stage in prediabetes is associated with increase in level of adipokines and pro-inflammatory cytokines. Physical activity promotion considered as a first-line therapeutic strategy to treat prediabetes. We have conducted the systematic review and meta-analysis to strengthen the evidence on the impact of physical activity promotion on inflammatory markers in prediabetes. Methods Studies were identified using electronic search and manual search techniques by choosing keywords for prediabetes, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
0
12
0
2
Order By: Relevance
“…We did not measure or take account of physical activity or fitness, which is a limitation of our study, as the influence of exercise on leptin and adiponectin is well established: A meta-analysis of exercise interventions in children with obesity ( 40 ) and others in adults with pre-diabetes ( 41 ) and obesity ( 42 ) have described similar effects on adipokines as we have found here, but of lower magnitude. By quantifying physical activity and fitness, future studies could more robustly determine the mechanistic basis for improvements in metabolic health with dietary and physical activity components of lifestyle modification.…”
Section: Discussionmentioning
confidence: 87%
“…We did not measure or take account of physical activity or fitness, which is a limitation of our study, as the influence of exercise on leptin and adiponectin is well established: A meta-analysis of exercise interventions in children with obesity ( 40 ) and others in adults with pre-diabetes ( 41 ) and obesity ( 42 ) have described similar effects on adipokines as we have found here, but of lower magnitude. By quantifying physical activity and fitness, future studies could more robustly determine the mechanistic basis for improvements in metabolic health with dietary and physical activity components of lifestyle modification.…”
Section: Discussionmentioning
confidence: 87%
“…If on the one hand, the literature indicates that the practice of physical exercise has been associated with a significant increase in adiponectin in children (Sirico et al, 2018;García-Hermoso et al, 2017;Jamurtas et al, 2015) on the other hand, several meta-analysis studies and systematic review, reported inconsistent results in the pediatric population, without elevation of adiponectin after physical exercise program (Jadhav et al, 2021;Bouassida et al, 2010;Simpson & Singh, 2008;Direcnet, 2008;Kelly et al, 2007). In a meta-analysis studies that measured adiponectin levels after three months, four months and one year of intervention, with or without dietary or lifestyle modification, it was observed that physical exercise had no significant effect on adiponectin levels (Jadhav et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis studies and systematic review of randomized clinical trials that evaluated the outcome of physical exercise, adiponectin and pediatric obesity, pointed out that exercise was associated with a significant increase in adiponectin Research, Society and Development, v. 11, n. 3, e17811326429, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i3.26429 3 (Sirico et al, 2018;García-Hermoso et al, 2017;Jamurtas et al, 2015). On the other hand, inconsistent results have been reported in the pediatric population, with no elevation of adiponectin after a physical activity program (Jadhav et al, 2021;Bouassida et al, 2010;Simpson & Singh, 2008;Direcnet, 2008;Kelly et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This increase in sedentary to light activity over a ~ 13-year period resulted in a risk reduction of 4.3% per MET h/week for CVD mortality and 1.7% for CVD incidence [ 26 ]. Potential mechanisms for the dose-dependent response of exercise to decreased CVD risk include improved glycemic control [ 31 ], improved vascular health [ 29 , 32 , 33 ], and improved leptin sensitivity [ 34 ].…”
Section: Physical Activitymentioning
confidence: 99%